INDIGENOUS/ CULTURAL/SPIRITUAL HEALING PRACTICES: A REPORT OF INTERACTION WITH TRADITIONAL HEALERS IN OGUN STATE SOUTH WEST NIGERIA. - Larry Salako; Nurudeen Oyekola Ibrahim; Sunday Mauton Amosu (Student's Journal of Health Research, 2023)
Background: Traditional belief systems in Africa impact the perceptions, attitudes, and management of mental illness. Cultural beliefs play a major role in the diagnosis and treatment of many mental health problems. Aim: To assess the cultural beliefs and practices of traditional healers/herbalist in Ogun state South-west Nigeria Method: Traditional healers were invited for discussion to assess their beliefs and practices of management of people living with mental illness Outcome/ Result: The interaction with the healers revealed that they believed that mental illness results from spiritual attack and or hereditary. In treatment, they make use of herbal concoction with dosing depending on the severity of the illness. They place them in shackles and chains to prevent absconding.